Surface-Based Morphometry of Cortical Thickness and Surface Area Associated with Heschl's Gyri Duplications in 430 Healthy Volunteers - Marie, Damien (Front Hum Neurosci, 2016)
We applied Surface-Based Morphometry to assess the variations in cortical thickness (CT) and cortical surface area (CSA) in relation to the occurrence of Heschl's gyrus (HG) duplications in each hemisphere. 430 healthy brains that had previously been classified as having a single HG, Common Stem Duplication (CSD) or Complete Posterior Duplication (CPD) in each hemisphere were analyzed. To optimally align the HG area across the different groups of gyrification, we computed a specific surface-based template composed of 40 individuals with a symmetrical HG gyrification pattern (20 single HG, 10 CPD, 10 CSD). After normalizing the 430 participants' T1 images to this specific template, we separately compared the groups constituted of participants with a single HG, CPD, and CSD in each hemisphere. The occurrence of a duplication in either hemisphere was associated with an increase in CT posterior to the primary auditory cortex. This may be the neural support of expertise or great abilities in either speech or music processing domains that were related with duplications by previous studies. A decrease in CSA in the planum temporale was detected in cases with duplication in the left hemisphere. In the right hemisphere, a medial decrease in CSA and a lateral increase in CSA were present in HG when a CPD occurred together with an increase in CSA in the depth of the superior temporal sulcus (STS) in CSD compared to a single HG. These variations associated with duplication might be related to the functions that they process jointly within each hemisphere: temporal and speech processing in the left and spectral and music processing in the right.